PERAN LINGKUNGAN TERHADAP PERKEMBANGAN BAHASA ANAK - Lilis Sumaryanti (Muaddib: Studi Kependidikan dan Keislaman, 2017)
The environment is one of the factors that have leverage quite big for the development of a language children. Because with the environment therefore his can carry on with his routine well without the difficulty in interact .A stimulus obtained a son through neighborhood is influential on the development of language children .Stimuli which are received in slowly will affect the development of a language children .The stimulus of the old its closest he will be processed by the son so as to make such a child matured in mindset , pattern of , and the pattern said .The role of parents so important demanding parents to cautious and careful in teach his son .Parents need to understand steps the development of a language on child to be able to provide a stimulus on stage of development in accordance with age. The development of a language is one of indicators to cognitive development a child , this relates to the success of or keterlambatannya in thinking and communicate in the area .A child who was said to be slow in speaking can affect the ability connection in day-to-day in person or social environment , it is to get the difficulty of learning , sociable , and activities work other when mature later. The factors that can affect the development of a language children between other: (1) brain development and intelligence , (2) sexes , (3) of the physical condition , (4) family environment , (5) the condition of the economy , ( 6 ) setting social / area culture , (7) bilingualism (2 language).